Short Communication: Biodegradable of bio-composites made from Polylactid Acid (PLA) and cellulose fibers from oil palm empty fruit bunch - YULIATI INDRAYANI; LISMAN SURYANEGARA; SAERI SAGIMAN; EMI ROSLINDA; MARWANTO MARWANTO (Smujo International, 2019)
Indrayani Y, Suryanegara L, Sagiman S,, Roslinda E, Marwanto. 2019. Short Communication: Biodegradable of bio-composites made from Polylactic Acid (PLA) and cellulose fibers from oil palm empty fruit bunch. Nusantara Bioscience 11: 8-11. Over the last two decades, plastic has become an integral part of people's everyday life. However, plastic is a material that difficult to be degraded in the environment. Due to environmental concern, it is indispensable to find environmentally friendly plastic materials. This study aimed to determine the biodegradable polymer composites manufacture from cellulose fibers of oil palm empty fruit bunches (OPEFB) and polylactic acid (PLA). Cellulose fibers from oil palm OPEFB were isolated by chemical methods. Polymer composites made by mixing cellulose fiber of oil palm OPEFB and PLA based on differences in the composition of the cellulose fiber of OPEFB. The composition used is 0 PHR, 5 PHR, 10 PHR, 15 PHR, and 20 PHR. Results showed that polymer composite with higher composition of cellulose fiber of OPEFB more easily degraded in the environment. There are no significant differences in biodegradable between 15 PHR and 20 PHR, neither among 10 PHR, 5 PHR and control. At higher cellulose fiber of OPEFB content, 20 PHR, polymer composite was the most degraded in the environment.